Predictors of castration‐resistant prostate cancer after dose‐escalated external beam radiotherapy. Issue 2 (18th October 2014) - Spratt, Daniel E.; Zumsteg, Zachary S.; Pei, Xin; Romesser, Paul B.; Yamada, Josh; Kollmeier, Marisa A.; Woo, Kaitlin; Zhang, Zhigang; Zelefsky, Michael J.
<x xml:space="preserve">Abstract</x> BACKGROUND Castration‐resistant prostate cancer (CRPC) is a near uniformly fatal form of prostate cancer; however, information on time to development and predictors for progression to CRPC is limited. We report a detailed longitudinal study for development of CRPC in men initially treated with external beam radiotherapy (EBRT). METHODS During 1991–2008, 2, 478 patients with clinically localized prostate cancer were treated with dose‐escalated EBRT at a single institution. The primary objective was to determine predictors of CRPC among men who failed definitive EBRT and progressed to salvage androgen‐deprivation therapy (ADT). CRPC was defined as castrate levels of testosterone (<50 ng/dl) with progressive biochemical or radiographic disease. RESULTS For the entire cohort (n = 2, 478), the 10‐year cumulative incidence rate for developing CRPC was 9.9%. For those that progressed to salvage ADT (n = 362), the 7‐year cumulative incidence rates for developing CRPC from time of salvage ADT was 33.7%. Amongst this cohort, multivariable analysis demonstrated that PSA doubling‐time (continuous; hazard ratio [HR], 0.98 [0.97–0.99], P < 0.001), higher Gleason score (HR, 1.96 [1.12–3.43]; P = 0.034), and duration of ADT at time of EBRT (continuous; HR, 1.02 [1.01–1.03]; P = 0.007) were associated with development of CRPC. CONCLUSIONS This represents the first report of predictors of CRPC for patients treated with modern dose‐escalated EBRT. We demonstrate that among the minority of patients not initially cured after EBRT, those treated with longer‐course ADT have higher rates of resistance to the re‐introduction of ADT. Future trials will need to test this subgroup with more aggressive or alternative forms of salvage therapies. Prostate 75:175–182, 2015. © 2014 Wiley Periodicals, Inc.